Diseases of Cassia species--a review - Lenné, Jillian M. (1990)
A wide range of fungi, two bacteria and several viruses and nematodes have been recorded throughout the tropics on a group of Cassia species defined as taxonomically and geographically related to Cassia rotundifolia. Although limited information was found on the relative importance of these pathogens, the fungi Alternaria cassiae, Corynespora cassiicola, Phomopsis cassiae, Pseudocercospora nigricans, Pseudoperonospora cassiae and Ravenelia berkeleyii and the viruses Cassia Mild Mosaic, Cassia Yellow Blotches and Cassia Yellow Blotch are considered the most serious. Specific recommendations are made to evaluate the reaction of C. rotundifolia cv. Wynn to these pathogens. The attention of Australian pasture scientists is drawn to recent plans to develop mycoherbicides for controlling pantropical Cassia weeds and the implications of their use in South-east Asia and the south-west Pacific.